KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN MAMUJU UTARA - Rahmatia, Rahmatia (Katalogis, 2016)
The goal in this study to mengetahui kinerja employees in Regional Development Planning Agency of North Mamuju regency. This type of qualitative research. The informants employees in Regional Development Planning Agency of North Mamuju regency, with the technique of determining the informant is purposive sampling. Data collection methods include observation, interviews and documentation, while the technique of data analysis include data reduction, data presentation, and conclusion (verification). The results showed that the employee has not fully have the ability because of the shortage of human resources who are less supportive so membua tpegawa ikurang understand the duties and less professional in their work. While motivas employees to do the job is not maximized because there are employees who must be suppressed and ruled by superiors at work, as well as the persistence of the employees should be given the training, guidance and education to support the quality of his work. But in terms of infrastructure and facilities, employees have been supported by it, other than that pegaai also receive additional incentives in the form of employee income.